2020
DOI: 10.1016/j.psychres.2020.113175
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 distresses the depressed while schizophrenic patients are unimpressed: A study on psychiatric inpatients

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 6 publications
1
27
1
3
Order By: Relevance
“…We did not find any difference in diagnostic groups previously ( Itrat et al, 2020 ). It is possible that stress perception ( Holzle et al, 2020 ) and changes to social supports and isolation ( Kozloff et al, 2020 ) could have contributed to psychological deterioration during the prolonged lockdown and thus leading to increased admissions for mood and psychotic disorders. Further, the changed operation of community psychiatric services in Melbourne during the lockdown, e.g., reduced outreach services and difficulties of patients adapting to digital platforms, could have increased social isolation and stress and thus leading to increased admissions for psychotic disorders and mood disorders.…”
Section: Discussionmentioning
confidence: 99%
“…We did not find any difference in diagnostic groups previously ( Itrat et al, 2020 ). It is possible that stress perception ( Holzle et al, 2020 ) and changes to social supports and isolation ( Kozloff et al, 2020 ) could have contributed to psychological deterioration during the prolonged lockdown and thus leading to increased admissions for mood and psychotic disorders. Further, the changed operation of community psychiatric services in Melbourne during the lockdown, e.g., reduced outreach services and difficulties of patients adapting to digital platforms, could have increased social isolation and stress and thus leading to increased admissions for psychotic disorders and mood disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Another cross-sectional study conducted in India found that 30% of individuals with SMI reported a re-emergence of psychiatric symptoms during COVID-19 lockdown ( Muruganandam et al., 2020 ). Finally, there is also some suggestion of a differential impact across diagnoses such that individuals with affective disorders report greater COVID-19-related stress relative to individuals with schizophrenia spectrum illnesses ( Hölzle et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another study found a generally low level of knowledge of COVID-19, lower compliance with health regulations and a lower level of anxiety regarding COVID-19 in comparison to the general population (4). Attempts to test the differential impact of the pandemic suggest that people with affective disorders are far more affected by the restrictions imposed by COVID-19, whereas people with psychotic disorders are less affected (5,6) Specific population groups may be especially vulnerable to stress resulting from the COVID-19 crisis. Psychiatric patients have more precarious employment (7); smaller social networks (8); lower health literacy (9); greater physical vulnerability via higher rates of obesity (10), and smoking (11,12).…”
Section: Introductionmentioning
confidence: 99%